A net +1 frameshift permits synthesis of thymidine kinase from a drug-resistant herpes simplex virus mutant. - Hwang, C B (1994)
Clinical resistance to antiviral drugs requires that a virus evade drug therapy yet retain pathogenicity. Thymidine kinase (TK)-negative mutants of herpes simplex virus are resistant to the drug, acyclovir, but are attenuated for pathogenicity in animal models. However, numerous cases of clinical resistance to acyclovir have been associated with viruses that were reported to express no TK activity. We studied an acyclovir-resistant clinical mutant that contains a single-base insertion in its tk gene, predicting the synthesis of a truncated TK polypeptide with no TK activity. Nevertheless, the mutant retained some TK activity and the ability to reactivate from latent infections of mouse trigeminal ganglia. The mutant expressed both the predicted truncated polypeptide and a low level of a polypeptide that comigrated with full-length TK on polyacrylamide gels and reacted with anti-TK antiserum, providing evidence for a frameshifting mechanism. In vitro transcription and translation of mutant tk genes, including constructs in which reporter epitopes could be expressed only if frameshifting occurred, also gave rise to truncated and full-length polypeptides. Reverse transcriptase-polymerase chain reaction analysis coupled with open reading frame cloning failed to detect alterations in tk transcripts that could account for the synthesis of full-length polypeptide. Thus, synthesis of full-length TK was due to an unusual net +1 frameshift during translation, a phenomenon hitherto confined in eukaryotic cells to certain RNA viruses and retrotransposons. Utilization of cellular frameshifting mechanisms may permit an otherwise TK-negative virus to exhibit clinical acyclovir resistance.